Cu(II) removal onto fungal derived biosorbents: Biosorption performance and the half saturation constant concentration approach - Tay, C.C.; Liew, H.H.; Yong, S.K.; Surif, S.; Redzwan, G.; Abdul-Talib, S. (International Journal of Research in Chemistry and Environment, 2012)
This study investigates the removing of Cu(II) using Pleurotus ostreatus fungal and Pleurotus ostreatus spent mushroom compost. In these batch biosorption experiments, the half saturation constant of biosorption was determined through Langmuir Linearization 1 plot of biosorbent concentration. This new approach was employed to minimize the use of biosorbent and to obtain results in shorter time. The half saturation constant of Cu(II) biosorption was 0.36 g for fungal Pleurotus ostreatus and 0.7 g for Pleurotus ostreatus spent mushroom substrate. There were three optimum operational parameters undertaken, which were the initial pH of 6, contact time of 10 minutes and 50 mg/L of initial Cu(II) concentration. These parameters were found to have produced results that clearly fitted the Langmuir and Freundlich isotherms, which also matched the pseudo second-order kinetic better than they do pseudo first-order kinetic. These implied that chemisorptions, complexation and ion exchange play a vital role in biosorption mechanism. In the same vein, the results of the FTIR analysis showed that the carboxyl, hydroxyl and amide group of lignocelluloses, chitin and proteins could be hypothesized that they were the functional groups involved in Cu(II) biosorption, in keeping with the findings shown by the said isotherms. Therefore, these biosorbents deem to be highly potential to be developed into a low impact, environment-friendly sustainable technology to remove heavy metals.